Konvergensi Pendapatan Provinsi Jawa Timur: Pendekatan Panel Kota/Kabupaten Periode 2000-2013 - Rasyid, Mohtar (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252), 2017)
This study aims to analyze the growth profile among the districts in East Java since decentralization in 2000. The main issues analyzed are economic inequality in East Java province during the period 2000 - 2013. Several previous studies indicate that decentralization did not have a significant impact on equity. To test the hypothesis of convergence or divergence, this study uses research framework introduced by Barro. The results show that regional income among regions in East Java tends to be convergent. OLS Tests shows that the convergence hypothesis has not been proven. After correcting specific regional factors that are formulated through a panel data analysis approach, the convergence hypothesis can be proven quite significant. In other words, there is a potential that the economic gap between regions has narrowed. From internal point of view, East Java's economy can be said to be relatively safe because there are indications that the gap between regions are diminishing. After the determinants of growth can be identified, the expected regional disparities will be more rapidly eliminated.
Keywords: konvergensi, pendapatan regional, otonomi daerah, analisis panel